2002
DOI: 10.1108/09540910210444719
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth behaviour of lead‐containing and lead‐free solders

Abstract: Fatigue crack growth (FCG) tests on lead‐containing solders and lead‐free solders have been carried out at frequencies ranging from 0.01 to 10 Hz and stress ratios in the range 0.1–0.7. The FCG resistance of lead‐free solders was found to be superior to that of lead‐containing solders. For both types of solder, cycle dependent behaviour is dominant for the tests at low stress ratios and high frequencies, while time‐dependent effects become important at high stress ratios and low frequencies. For cycle dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The research has demonstrated that Bi additions to SAC alloys improve their mechanical performance, increasing solder joint shear strength [25][26][27][28], thermal fatigue resistance [29] and improve the drop-impact performance [29]. This is reportedly due to solid solution strengthening of βSn with Bi and/or precipitation strengthening with (Bi) phases [25,28,[30][31][32]. Additionally, Bi additions have been shown to improve wetting and spreading of lead-free solders [27,29,33] and to lower their liquidus temperature [34].…”
Section: Introductionmentioning
confidence: 98%
“…The research has demonstrated that Bi additions to SAC alloys improve their mechanical performance, increasing solder joint shear strength [25][26][27][28], thermal fatigue resistance [29] and improve the drop-impact performance [29]. This is reportedly due to solid solution strengthening of βSn with Bi and/or precipitation strengthening with (Bi) phases [25,28,[30][31][32]. Additionally, Bi additions have been shown to improve wetting and spreading of lead-free solders [27,29,33] and to lower their liquidus temperature [34].…”
Section: Introductionmentioning
confidence: 98%
“…Among them, Sn-Ag-Cu-Bi is regarded as one with high quality and performance and can meet the requirement electronic packaging. Researches have been reported on their fatigue property and joint performances [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] It has been reported that microstructure is significantly changed by recrystallization that occurs in areas with high strain energy in Pb-free solder interconnects during thermal cycling, and cracks are initiated and propagated intergranularly in the recrystallized microstructure, leading to the final failure of the solder interconnects. [5][6][7][8][9][10][25][26][27][28] Recrystallization can be defined as the formation of a new grain structure in a deformed material by the formation and migration of high-angle grain boundaries driven by the stored energy of deformation.…”
Section: Introductionmentioning
confidence: 99%